Cenas antigas em novo espetáculo: O processo de regulamentação da profissão de Educação Física - Silva, Maria Eleni Henrique da (2005)
The objective ofthis research was making a reflexive-descriptive rescue ofthe process of regulation of the profession of physical education, to understand the strikes in them, indicative of internal disputes for the prevalence of conceptions and projects of construction in this area. It also presented as specific objectives: a) identify the legitimated values, disclosed or occulted, in groups favorable or against to the process and b) verify the positive and negative points of this processo For that, we looked for the theory by Pierre Bourdieu, instrumental theoretical-rnethodological to explain the relations in the physical education field among the groups against or favorable to the regulation, to understand the discussions, disputes and the interests which these two groups discuss about. Thus, we used, mainly, the concepts of field, habitus, power and symbolic capital. In the second moment, the historical process is reconstituted, from the bibliography about the theme, in order to evidence the changes made by that process which makes the reconfiguration in the physical education field. To understand the discussion in the two main groups, we used two fundamental sources: the written and the oral sources. Four interviews and three questionnaires were made to collect the data; to analyze and interpret the data was made the method of content analysis. In the result ofthe research were found: a) the political dispute for keeping the hegemony in the physical education field, among the favorable and against groups to this process of regulation, in its different approaches about what is physical education, in relation to health and education; b) in the regulation process, symbolic systems are produced; c) when instituted the "physical education professional", is clear the structural laws which delimit or reconfigure this area, showing the social domination required by the profile of these professionals; d) among lhe favorable and against the regulation process, there is a relation of power about the group of researchers and students in those ones who "makes" physical education. 1t was concluded that the process of regulation to the education physical professional, when it was established, it brought back old disputes about the discussions between the "conservatives" and "progressists", developed in the 80's. The regulation process brought back old disputes to new scenerys, relived intense conflicts without dialogues, with speeches and arguments qhich were supposed to disqualify the speech which were favorable or against the regulation.